The Effect of Education Model in Physical Education on Student Learning Behavior - Chu, Yongchao; Chen, Chang; Wang, Guoquan; Su, Fuzhi (Frontiers in Psychology, 2022)
This research explores the effect of the sports education model implemented in physical education on college students’ learning motivation and outcomes. The sports education model was compared with traditional physical education teaching as a control group. Participants were 60 college students in two classes. The ARCS (Attention, Relevance, Confidence, Satisfaction) Learning Motivation Scale, the Physical Education Affection Scale and a learning sheet were used for pre-and post-test comparison. Quantitative analysis was carried out on the post-test data using a dependent sample t-test and an independent sample t-test. The study found that: (1) the students in the sports education model group showed clear progress in learning motivation, affection, cognition, and behavior, whereas the students in the traditional physical education group showed clear progress in cognition but no significant improvement in learning motivation, affection or behavior; (2) the sports education model group is clearly superior to the traditional physical education group in terms of learning motivation, affection, cognition, and behavior. This research shows that students are highly receptive to the sports education model, with a positive attitude and a high degree of motivation to learn to actively change their sports behavior. The sports education model brings several benefits: (1) it is an effective teaching method; (2) students’ sense of responsibility, leadership, and participation can be improved; (3) the preliminary homework and course structure descriptions take more time to compose, but can better guide students' motivation for learning physical education and can enhance teachers' professional growth.